FRI0546 Multiple Versus Single Ultrasound Guided Suprascapular Nerve Block in Treatment of Frozen Shoulder in Diabetic Patients. (9th June 2015) - Mortada, M.; Ashour, M.M.; Abbas, S.F.; Ammar, H.A.; Ezzeldin, N.; Salama, N.A.
Abstract : Background: Frozen shoulder, is characterized by pain and significant loss of both active range of motion and passive range of motion of the shoulder. Suprascapular nerve block is used with increasing frequency by anesthetists and rheumatologists in the management of frozen shoulder. There are no evidences in the literature that can determine how many blocks to use and the interval between them (1). Objectives: To compare between single and multiple (nine) SSNB in the treatment of diabetic frozen shoulder. Methods: This study included 96 type 2 diabetic patients with frozen shoulder divided into 2 equal groups. Patients in group1 were subjected to single SSNB in addition to an exercise program 3 times per week for 3 weeks. Patients in group 2 were subjected to multiple (nine) SSNB 3 times per week in addition to the previous exercise program. Ultrasound was used to guide the needle during SSNB. Participants will be assessed at baseline (following recruitment) and then after 3 weeks, and 4 months. In addition to demographics, assessments included the following measures: The shoulder pain and disability index (SPADI), Patient global assessment using: Visual Analogue Scale, Night pain using: Visual Analogue Scale and Active range of movement was measured using a goniometer in three planes: abduction, internal, and external rotation. Results: Forty two patients completed the study group 1, but the number of patients in group 2 was forty patients. At the first follow up (after 3 weeks), there was a significant improvement of all parameters of SPADI scale (pain, disability and total), night pain and patient global assessment in both groups in comparison with the base line parameters (p≤0.001). But the improvement in group 2 in which we used the multiple injection protocol was significantly better than the improvement in group 1 in which a single injection protocol was used. Also at the second time point of follow up (after 4 months), all parameters in both groups showed a further improvement in comparison with the base line parameters but still there was a highly significant improvement in group 2 versus group1 (p≤0.001). Improvement of active range of motion (ROM) in all directions was highly significant in both groups at the 1st time points of follow up (after 3 weeks) in comparison with base line ROM measures and continue to improve at the 2nd time points of follow up (after 4 months). Conclusions: Course of multiple (nine) injections for suprascapular nerve block gave a better improvement than a single injection for suprascapular nerve block as regards pain, disability, active range of motion and patient global assessment. Up to the best of our knowlege this the first study to compare between different regimens of SSNB. References: Fernandes MR, Barbosa MA, Sousa AL, Ramos GC. Rev Bras Reumatol. 2012 Aug;52(4):616-22. Disclosure of Interest: None declared